Development of web-based system for soybean insect pests management: SOYBEAN INSECT PESTS MANAGEMENT SYSTEM - SAVITA KOLHE; AMAR NATH SHARMA (Journal of Oilseeds Research, 2020)
The paper describes the development of a web-based system for identification of soybean insects and their management. It presents the system design, development methodology, functionality and utility of the system. The user interface of the system is developed using ASP.NET and backend using SQL. It is designed using responsive web design so that the users can easily use the system on different devices with variable screen sizes-Desktops, Laptops, iPads, Tablets and Mobile phones. The system is accessible from the institute website https://iisrindore.icar.gov.in. It is very useful for farmers in taking right decision at right time in their fields. The users could identify the insects correctly with the image-based identification interface. The information in Hindi language will help farmers to easily understand the contents. The systemwas evaluated on eight user interface design features on 1-10 point scale. The overall average rating was more than 8 points indicating that most ofthe evaluators were satisfied with the user interface. It served as an effective IT tool for farmers to take appropriate and timely measures to minimize field losses due to insect attack.